The System for Determining the Tariff of Retribution at the Marine and Fisheries Service of Boalemo - wiwin biluwa; Syamsinah; Siske Anani (Journal of Economic, Business, and Administration (JEBA), 2022)
This study aims to find out the system for setting retribution rates at the Department of Marine Affairs and Fisheries of Boalemo Regency. This study uses a descriptive type of research with a qualitative approach. The data used in the form of targets and realizations obtained by the Department of Marine Affairs and Fisheries of Boalemo Regency for the 2017-2020 period with data collection techniques of observation, interviews and documentation. The results showed that the levy tariff determination at the Marine and Fisheries Service of Boalemo Regency showed that the levy rate on fish auctions charged to traders was 2.5% in accordance with regional regulations. Then the levy will be managed by the Department of Marine Affairs and Fisheries and then deposited into the regional treasury. And there are still obstacles in implementing the levy setting system for the Boalemo Regency Maritime Affairs and Fisheries Service, where the system for applying the levy tariff is sometimes not in accordance with the regulations that have been made, with fish imports from auction fishermen being less than optimal due to weather factors.